Education and prevalence of overweight and obesity among reproductive age group women in Ethiopia: analysis of the 2016 Ethiopian demographic and health survey data - Ayelign Mengesha Kassie; Biruk Beletew Abate; Mesfin Wudu Kassaw (BMC, 2020)
Abstract Background Globally, the prevalence of overweight and obesity is escalating, particularly among women and wealthier people. In many developed countries, overweight and obesity are more prevalent in persons with lower socioeconomic status. In contrast, studies in developing countries have reported a higher prevalence rate of overweight and obesity among women with higher educational status. Hence, this study aimed to assess the association between education and the prevalence of overweight and obesity among reproductive age group women in Ethiopia. Methods This cross-sectional study was done based on the 2016 Ethiopian demographic and health survey (EDHS) data. From the total 15,683 women participants of the 2016 EDHS, 2848 reproductive age group women aged 15-49 years old who had a complete response to all variables of interest were selected and retained for analysis. Data were analyzed using SPSS version 20 software program. Both descriptive and logistic regression models were used for analysis. Results The prevalence of overweight and obesity among the study participants was 11.5 and 3.4% respectively. The combined prevalence of overweight and obesity was 14.9%. From the total participants who are overweight and, or obese, majority, 83.3% were urban dwellers and the remaining 16.7% were rural dwellers. Education was positively associated with overweight and obesity among women. Besides, increased age, region, living in urban areas, being in rich quintile, increased frequency of watching television, and frequency of using internet were significantly associated with the odds of being overweight and obese among reproductive age group women in Ethiopia. Conclusions The prevalence of overweight and obesity among reproductive age group women in Ethiopia is increasing compared to previous studies. Education was found to be a risk factor for overweight and obesity among women. Hence, context based interventions on the prevention and control methods of overweight and obesity are required.